FCGR Genetic Variation in Two Populations From Ecuador Highlands—Extensive Copy-Number Variation, Distinctive Distribution of Functional Polymorphisms, and a Novel, Locally Common, Chimeric FCGR3B/A (CD16B/A) Gene - Moraru, Manuela; Perez-Portilla, Adriana; Al-Akioui Sanz, Karima; Blazquez-Moreno, Alfonso; Arnaiz-Villena, Antonio; Reyburn, Hugh T.; Vilches, Carlos (Frontiers in Immunology, 2021)
Fcγ receptors (FcγR), cell-surface glycoproteins that bind antigen-IgG complexes, control both humoral and cellular immune responses. The FCGR locus on chromosome 1q23.3 comprises five homologous genes encoding low-affinity FcγRII and FcγRIII, and displays functionally relevant polymorphism that impacts on human health. Recurrent events of non-allelic homologous recombination across the FCGR locus result in copy-number variation (CNV) of ~82.5 kbp-long fragments known as copy-number regions (CNR). Here, we characterize a recently described deletion that we name CNR5, which results in loss of FCGR3A, FCGR3B, and FCGR2C, and generation of a recombinant FCGR3B/A gene. We show that the CNR5 recombination spot lies at the beginning of the third FCGR3 intron. Although the FCGR3B/A-encoded hybrid protein CD16B/A reaches the plasma membrane in transfected cells, its possible natural expression, predictably restricted to neutrophils, could not be demonstrated in resting or interferon γ-stimulated cells. As the CNR5-deletion was originally described in an Ecuadorian family from Llano Grande (an indigenous community in North-Eastern Quito), we characterized the FCGR genetic variation in two populations from the highlands of Ecuador. Our results reveal that CNR5-deletion is relatively frequent in Llano Grande (5 carriers out of 36 donors). Furthermore, we found a high frequency of two strong-phagocytosis variants: the FCGR3B-NA1 haplotype and the CNR1 duplication, which translates into an increased FCGR3B and FCGR2C copy-number. CNR1 duplication was particularly increased in Llano Grande, 77.8% of the studied sample carrying at least one such duplication. In contrast, an extended haplotype CD16A-176V – CD32C-ORF+2B.2 – CD32B-2B.4 including strong activating and inhibitory FcγR variants was absent in Llano Grande and found at a low frequency (8.6%) in Ecuador highlands. This particular distribution of FCGR polymorphism, possibly a result of selective pressures, further confirms the importance of a comprehensive, joint analysis of all genetic variations in the locus and warrants additional studies on their putative clinical impact. In conclusion, our study confirms important ethnic variation at the FCGR locus; it shows a distinctive FCGR polymorphism distribution in Ecuador highlands; provides a molecular characterization of a novel CNR5-deletion associated with CD16A and CD16B deficiency; and confirms its presence in that population.